Cross-platform demonstrator combining spectrum sensing and a geo-location database - Dionísio, Rogério Pais (2012)
After the digital switchover, a secondary access of the so-called TV White Spaces should not interfere with primary users, such as DVB-T systems and local wireless microphone devices. One consensual method for secondary spectrum users to avoid interference is to combine geo-location database with spectrum sensing. This paper describes an experimental platform that combines wireless microphone sensors with a web-based geo-location database access. Software defined radios and Internet technologies are the enabling tools in use. From test trials in a real scenario, the platform was capable to update a list of vacant channel from the geo-location database, using reliable information from blind sensing algorithms.